Reconfiguring Economic Democracy: Generating New Forms of Collective Agency, Individual Economic Freedom and Public Participation. (August 2020) - Cumbers, Andrew; McMaster, Robert; Cabaço, Susana; White, Michael J
We seek to advance debate and thinking about economic democracy. While recognising the importance of existing approaches focused upon collective bargaining and workplace organisation, we articulate a perspective that emphasises the importance of individual economic rights, capabilities and freedoms at a time when established norms and protections at work are in retreat in many parts of the world. We outline a framework where both individual rights to self-government of one's own labour, as well as the right of all citizens to participate in economic decision-making, are emphasised. The framework identifies a set of underlying principles, prerequisites, critical spheres for intervention, progressive institutional arrangements, and policies in pursuit of an expanded agenda around economic democracy. In this way, economic democracy potentially empowers individuals and creates the basis for generating new and sustainable alliances that challenge elite dominance in contemporary capitalism.